Provenance of Ordovician and Devonian sandstones from southern Peru and northern Bolivia - U-Pb and Lu-Hf isotope evidence of detrital zircons and its implications for the geodynamic evolution of the Western Gondwana margin (14°-17°S) - Reimann Zumsprekel, Cornelia R. (2009)
páginas 236-237.